2018
DOI: 10.3390/ijerph15010089
|View full text |Cite
|
Sign up to set email alerts
|

Annual Direct Medical Costs of Diabetic Foot Disease in Brazil: A Cost of Illness Study

Abstract: The aim of this study was to estimate the annual costs for the treatment of diabetic foot disease (DFD) in Brazil. We conducted a cost-of-illness study of DFD in 2014, while considering the Brazilian Public Healthcare System (SUS) perspective. Direct medical costs of outpatient management and inpatient care were considered. For outpatient costs, a panel of experts was convened from which utilization of healthcare services for the management of DFD was obtained. When considering the range of syndromes included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
30

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 32 publications
1
52
0
30
Order By: Relevance
“…The management of chronic wounds is complex, time-consuming, and requires high level of resources [3], and can result in an important economic and public health burden, especially in low and middle income countries [13]. In Argentina healthcare is provided by both public and private sectors.…”
Section: Discusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The management of chronic wounds is complex, time-consuming, and requires high level of resources [3], and can result in an important economic and public health burden, especially in low and middle income countries [13]. In Argentina healthcare is provided by both public and private sectors.…”
Section: Discusionmentioning
confidence: 99%
“…Limited evidence is available on the costs of CLLU in Latin American countries. One study in Brazil with DFU showed an estimated average cost for outpatient management that range fromUS$400 to US$1,600 [13] and the average hospitalization cost per patient range from US$400 to US$2,700 [13]. Meanwhile, in Peru the annual cost per patient hospitalization range from US$1,022 to US$7,360 according to the treatment applied [14].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic wounds are reported to affect around 6.5 million patients just in USA; the estimated annually cost is more than US$ 25 billion for wound-related complications and healthcare system. In Brazil, the most populous country in Latin America, about 40 to 60% of non-traumatic lower limb amputations occur in diabetic patients; whereas, about 85% are related to foot ulcers [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, in addition to the comorbidities associated with diabetes, the increasing life expectancy of these patients also increases the incidence of these conditions [4]. In developing countries such as Brazil, evidence suggests that lifetime occurrence of diabetic ulcers is between 19% and 34% [5].…”
Section: Introductionmentioning
confidence: 99%
“…The health costs of treating chronic ulcers in diabetic patients with venous leg ulcers and diabetic foot ulcers are five times higher than in diabetic individuals with no ulcer [4,7]. Those costs are mainly related to hospitalizations, more frequent in diabetics, but also to the care costs of treatment and follow-up of outpatient clinical management [8][9][10][11].…”
mentioning
confidence: 99%